Effects of Poland's pro-export policy implementation in the context of the plan for responsible development: A preliminary comparative assessment - Zofia Wysokińska (Comparative Economic Research. Central and Eastern Europe, 2017)
The aim of this paper is to present the results of a preliminary assessment of Poland's export expansion policy in relation to the export of commodities, which is a result of the Government's Plan for Responsible Development, in the context of existing barriers and the external and internal conditions reported by small and medium-sized enterprises sector (SMEs). In the latest ranking of its competitive position in the global market for the period 2016-2017, Poland ranked 36th in the world. It should also be stressed that in this most recent world ranking Poland held the 16th position among EU Member States. A positive phenomenon in relation to Poland's foreign trade in 2016, as compared to previous years, was that the value of export exceeded import, which allowed for a turnover surplus of nearly EUR 4.8 billion, i.e. two times higher than in 2015. In 2016 (and also in the first half of 2017) there was a favorable diversification of Polish export, demonstrating an increase in export to non-EU markets of economically developed countries. After two years of relatively slow growth, export to this group of countries in 2016 increased by 5.6% (to EUR 12 billion), i.e. nearly 2.5 times faster than the total export. Despite the tariff-free and quota-free access to the single European market, there are still limits and barriers to the free movement of goods, and especially services. There are also many internal barriers in small and medium-sized enterprises' export to foreign markets, which limit their export expansion. Despite the gradual increase in export observed in recent years, the internationalization of non-Polish enterprises is still much lower than in Western European countries. As a result, the share of Polish SMEs in the EU market is one third smaller than the EU average.
Keywords: F13; F14; 330; export policy; Plan for Responsible Development; internal and external barriers; SME sector